Analisis Pengendalian Persediaan Bahan Baku Dengan Menggunakan Metode Economic Order Quantity (Eoq) Pada Pt. Bazt Inti Bersama - Virgi Triya (AKUNTANSI 45, 2024)
A very important component in the production process at the company is the raw material. To deal with market demand, accurate raw material inventory planning is needed to determine optimal and economical purchasing levels. This is to ensure that there are no excess or shortage of inventory, which allows for cost savings and disruption of raw material stockouts in the production process. The purpose of this study is to determine the management of existing inventory stock at PT. Bazt Inti Bersama, as well as to find out the optimal number of orders at the most economical cost using the Economic Order Quantity (EOQ) method, and the application of safety stock. This study uses a qualitative descriptive method with data collection techniques through library research, observation, interviews, documentation related to the research problems studied. The results showed that the raw material inventory control for fresh salmon at PT. Bazt Inti Bersama is quite good, but controlling raw material inventories using the economic order quantity (EOQ) method has been proven to be able to reduce the cost of inventories used with a difference in costs of 19,074,116 rupiah. So it can be more economical. Meanwhile, the safety stock needed by the company requires 5,324 kg.